Are Non-woven Gowns Safe for Dental Professionals? A Preclinical Double-Blind Study - Barboza, Eliane Porto; dos Santos, Gustavo Oliveira; Montez, Caroline; Sendra, Luiza Abreu; Vieira, Esio Oliveira; Ferreira, Vinicius Farias (Frontiers in Dental Medicine, 2020)
With the advent of the COVID-19 pandemic, the risk of dental professional’s infection increases exponentially due the aerosol-generating procedures. The protective performance of dental professional gown fabrics is a major challenge against microorganisms and aerosols. This study evaluated whether dental aerosol-generating procedures have the potential to pass through three different nonwoven weights (40g/m2, 60 g/m2, 80 g/m2). Single and folded formats of each weight were analyzed. The positions of the mannequin and the high-speed handpiece were standardized. The nonwoven samples were placed over a sheet of sulfite paper and fixed on a marked position of a standardized smooth surface, 10 cm away from the end of the mannequin's head, simulating the dental professional body. For better visualization, the water used in the equipment was tinted with water-soluble red artificial dye. Blind to the nature of the groups one researcher started the 5 uninterrupted minutes of aerosol production. The sheets were randomized coded, so that the samples could not be identified by the evaluator. Another researcher, blind to the tests, scanned all sheets and the images were analyzed by ImageJ software. The groups showed significant differences (p <0.01). Except for the folded 80g/m2, all groups presented pigmented mean areas ranging from 16.18% (60g/m2 folded) to 35.68 (40g/m2 single), suggesting that the one layer nonwoven samples were not effective as barriers for 5 min uninterrupted aerosol spray. Dental procedures exceeding the studied time may provide different results with the nonwoven 80g/m2 folded. Dental health workers, who are exposed to daily aerosols procedures should be aware of the exact specification and performance of the fabrics used in the manufacturing of their disposable garments. If the use of an impermeable PPE is not possible during aerosol-generating procedures, a plastic garment associated with a disposable PPE should be worn, as recommended by the World Health Organization